Influence of Side Uncertainty on Knee Kinematics of Female Handball Athletes During Sidestep Cutting Maneuvers - Souza Bedo, Bruno Luiz; Cesar, Guilherme Manna; Moraes, Renato; Mariano, Fabio Pamplona; Palucci Vieira, Luiz Henrique [UNESP]; Andrade, Vitor Luiz; Pereira Santiago, Paulo Roberto (Human Kinetics Publ Inc, 2021)
Noncontact anterior cruciate ligament ruptures generally occur during unanticipated sidestep cutting maneuvers when athletes have their visual attention focused on the opponent. The authors investigated the influence of uncertainty related to the side to perform the sidestep cutting maneuver on knee kinematics of female handball athletes. A total of 31 female handball athletes performed the sidestep cutting maneuver during anticipated and uncertain conditions. During the uncertain condition, visual cues indicated the direction of the reactive sidestep cutting maneuver. Between-condition differences were compared using the Student t test for paired samples calculated with statistical parametric mapping. Lower knee flexion angle was detected during the uncertain condition compared with the anticipated condition for the nondominant limb (0%-8% of the sidestep cycle). Knee abduction was larger during the uncertain condition for both the dominant (15%-41% of the sidestep cycle) and nondominant (0%-18% of the sidestep cycle) limbs compared with the anticipated condition. The nondominant leg showed higher knee abduction (36%-68% of the sidestep cycle) during the uncertain condition compared with the anticipated condition. The athletes' approach velocity was slower during the uncertain condition. The uncertain condition impacted knee kinematics and potentially positioned the joint at greater risk of injury by decreasing the flexion angle in the nondominant leg and increasing the joint valgus bilaterally.
Keywords: injury risk; change of direction; ACL; statistical parametric mapping